The mediating effect of nomophobia in the relationship between problematic social media use/problematic smartphone use and psychological distress among university students - Tung, Serene En Hui; Gan, Wan Ying; Poon, Wai Chuen; Lee, Ling Jun; Ruckwongpatr, Kamolthip; Kukreti, Shikha; Griffiths, Mark D.; Pakpour, Amir H.; Lin, Chung-Ying (Routledge, 2025)
As smartphones and social media become more common, the psychological impact on university students has garnered increasing research attention. The present study examined nomophobia as the mediator in the relationship between problematic social media use (PSMU)/ problematic smartphone use (PSU), and psychological distress among university students during the COVID-19 pandemic. Of the 622 Malaysian university students recruited through online survey, socio-demographic information, Bergen Social Media Addiction Scale (BSMAS), Smartphone Application-Based Addiction Scale (SABAS), Nomophobia Questionnaire (NMPQ) and Depression, Anxiety and Stress Scale-21 (DASS-21) were completed. To analyze mediation effects, partial least squares structural equation modelling (PLS-SEM) was used. PSMU, PSU and psychological distress were found to be positively related to nomophobia. Nomophobia was a significant mediator between PSMU/PSU and psychological distress. Findings appear to highlight the importance of nomophobia in increasing psychological distress among young adults. Future research could examine these relationships longitudinally to better understand the relationship for effective interventions for the improvement of psychological well-being of young adults navigating the challenges of modern technology.